Analysis of factors contributing to variation in the C57BL/6J fecal microbiota across German animal facilities - Günther, Claudia; Rausch, Philipp; Basic, Marijana; Batra, Arvind; Bischoff, Stephan C.; Blaut, Michael; Clavel, Thomas; Gläsner, Joachim; Gopalakrishnan, Shreya; Grassl, Guntram A.; Haller, Dirk; Hirose, Misa; et al. (International Journal of Medical Microbiology, 2016)
The intestinal microbiota is involved in many physiological processes and it is increasingly recognized that differences in community composition can influence the outcome of a variety of murine models used in biomedical research. In an effort to describe and account for the variation in intestinal microbiota composition across the animal facilities of participating members of the DFG Priority Program 1656 "Intestinal Microbiota", we performed a survey of C57BL/6J mice from 21 different mouse rooms/facilities located at 13 different institutions across Germany. Fresh feces was sampled from five mice per room/facility using standardized procedures, followed by extraction and 16S rRNA gene profiling (V1-V2 region, Illumina MiSeq) at both the DNA and RNA (reverse transcribed to cDNA) level. In order to determine the variables contributing to bacterial community differences, we collected detailed questionnaires of animal husbandry practices and incorporated this information into our analyses. We identified considerable variation in a number of descriptive aspects including the proportions of major phyla, alpha- and beta diversity, all of which displayed significant associations to specific aspects of husbandry. Salient findings include a reduction in alpha diversity with the use of irradiated chow, an increase in inter-individual variability (beta diversity) with respect to barrier access and open cages and an increase in bacterial community divergence with time since importing from a vendor. We further observe a high degree of facility-level individuality, which is likely due to each facility harboring its own unique combination of multiple varying attributes of animal husbandry. While it is important to account and control for such differences between facilities, the documentation of such diversity may also serve as a valuable future resource for investigating the origins of microbial-driven host phenotypes.
Keywords: 16S rRNA gene; C57BL/6J; Gut microbiota; Mouse husbandry